Moral Competence, Personality, and Demographic Characteristics: A Comparative Study - Karamavrou, Sofia; Mouratidou, Katerina; Evaggelinou, Christina; Koidou, Irini; Parisi, Ioanna (ETHICS IN PROGRESS, 2016)
The development of moral competence is affected by both internal and external factors and has been researched by many scientists. The present study investigated a) whether the five factors of personality, gender and geographical area would affect ones’ moral competence, b) whether the personality factors Openness to Experience, Conscientiousness and Agreeableness would be correlated positively with moral competence in everyday life, whereas Extraversion and Neuroticism would be correlated negatively with morality, c) if there will be differences in students’ moral competence exhibited in everyday life and that expressed in PE/sports framework and d) whether type of school, factors of personality, as well as moral competence exhibited in sports-framework would all be significant factors for the interpretation of a student’s moral competence. The sample consisted of 331 junior high students (7th and 8th graders) (Mage = 12.47, SD = 0.740), who were given the Moral Competence Test Greek Version (Mouratidou et al. 2003), the Moral Judgment Test in Physical Education(Mouratidou et al. 2008), and the Inventory of Child Individual Differences (Besevegkis & Pavlopoulos 1998). The results indicated that of the five-factor personality model only Conscientiousness can affect moral reasoning ability in everyday life and that the type of school can account for less than 5% of variance when predicting moral competence in high school students.